If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -10y = 63 + 5y Solving 18 + -10y = 63 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 18 + -10y + -5y = 63 + 5y + -5y Combine like terms: -10y + -5y = -15y 18 + -15y = 63 + 5y + -5y Combine like terms: 5y + -5y = 0 18 + -15y = 63 + 0 18 + -15y = 63 Add '-18' to each side of the equation. 18 + -18 + -15y = 63 + -18 Combine like terms: 18 + -18 = 0 0 + -15y = 63 + -18 -15y = 63 + -18 Combine like terms: 63 + -18 = 45 -15y = 45 Divide each side by '-15'. y = -3 Simplifying y = -3
| 2x^2=242 | | 2h+4=25-h | | d-(-6)=15 | | 5x^2-25x+30=0 | | 20x-19=16x+14 | | 12+36=13t-7y | | 9=10r-16+5r | | 4d-11=2d+y | | (3+x)3=x+19 | | 5x+8y=27 | | 6a+10b-20= | | -55=18+s | | 11x-4y=22 | | x^2+2x-440=0 | | 35=27+c | | -5(n-6)=-4n-(9n-6) | | e+16=18 | | 5Z^2-75=0 | | 0.5(x-2)+2=0.375(3x-4) | | 0.6a+2=0.3(4a+1) | | -4j-(-5)=-91 | | -x+4(3x+2)=-8 | | 11x-33y=99 | | 5a-2(a-5)=19 | | .666666x-5=5 | | b-6=8 | | 4j-(-5)=91 | | x(5x+8)=4 | | 6=1.2d | | 9r=45 | | 10(8+c)=230 | | 0=5x^2-25x+30 |